2007
DOI: 10.1007/bf03016635
|View full text |Cite
|
Sign up to set email alerts
|

Case series: Septa can influence local anesthetic spread during infraclavicular brachial plexus blocks

Abstract: Purpose: To ultrasonically identify the presence of septae within the neurovascular sheath and to assess their effect on local anesthetic spread when performing infraclavicular brachial plexus blocks.Clinical features: Thirty ASA status I and II patients scheduled for minor hand surgeries were enrolled in the study. Ultrasound guided infraclavicular brachial plexus blocks were performed on 28 patients. The images of the local anesthetic spread and the effect of the septum within the neurovascular sheath were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 13 publications
1
26
0
2
Order By: Relevance
“…This was performed with a technique similar to that described by Sandhu [14] and modified by Dingemans [6] and Morimoto [7]. Patients were supine with the arm to the side and head turned slightly to the contralateral side.…”
Section: Infraclavicular Groupmentioning
confidence: 99%
See 2 more Smart Citations
“…This was performed with a technique similar to that described by Sandhu [14] and modified by Dingemans [6] and Morimoto [7]. Patients were supine with the arm to the side and head turned slightly to the contralateral side.…”
Section: Infraclavicular Groupmentioning
confidence: 99%
“…It has been suggested that injection of local anaesthetic at this point results in a reliable, rapid onset block within minutes [3]. On the other hand, other workers have reported excellent results with the lateral sagittal infraclavicular approach [6], specifically when local anaesthetic is placed deep to the septum posterolateral to the axillary artery [7,8].Block onset time has clinical importance in many settings in that it can influence the feasibility of brachial plexus block (compared with general anaesthesia) as the primary anaesthesia for minor wrist and hand surgery. Therefore, the primary aim of this study was to test the hypothesis that…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These anatomical variants not only meddle with the medial trunk block, but also with the posterior one. Failed or partial blocks may also be caused by the presence of muscular intersepta, tendinous structures or septa within the neurovascular sheath that can influence the pattern of local anesthetic spread [8]. Other possible variables are related to the injection duration of LA bolus, ultrasonographic imaging difficulties in visualizing infraclavicular region and anatomical structures in high BMI patients that complicate the visual control of LA injection.…”
Section: Discussionmentioning
confidence: 99%
“…The reference point for USG-ICB is the axillary artery, even though the heterogeneous brachial plexus sonography, the presence of septa within the neurovascular sheath [8], and the absence of a clear nervous target for spreading local anesthetics complicate the study of a minimum effective anesthetic volume. However, the single-injection of anesthetics with the "double bubble" technique [9] assures a high success blockade rate [10].…”
Section: Introductionmentioning
confidence: 99%